Effect of Solar Parameters on Geomagnetic Storm Formation in the Ascending Phase of the 25th Solar Cycle - Can, Zehra; Erdag, Hasan Safak (SPRINGER, 2025)
In this paper, starting from solar storms, which are the main cause of geomagnetic storms, the effects of the speed (v) and density (Np) of solar plasma coming to the Earth on geomagnetic storms are investigated. During the ascending phase of the 25th solar cycle (2021 - 2022), various geomagnetic storms from G1 to G4 were examined. Multiple linear regression models are created to examine the effects of solar parameters that cause changes in geomagnetic storm processes. The effects of the speed and charge density of solar wind, coronal mass ejections (CMEs), corotating interaction regions (CIRs), and CME-CME interactions on the Dst index, which reflects disturbances in the Earth's magnetic field and the scale of geomagnetic storms, are statistically analyzed. It is determined that a one-unit change in speed in 82 geomagnetic storms in the statistical models created a decrease in Dst of approximately -0.25 nT. In contrast, it is determined that a unit increase in particle density also reduces the effect and duration of a geomagnetic storm. However, if there is an increase in density during the main phase of the storm, then the storm level increases. We believe that our results will significantly contribute to predicting the formation of geomagnetic storms and their possible effects on space weather.
Keywords: INTERPLANETARY MAGNETIC-FIELD; ORIGIN; Astronomy & Astrophysics